2006
DOI: 10.1523/jneurosci.5509-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Slow State Transitions of Sustained Neural Oscillations by Activity-Dependent Modulation of Intrinsic Excitability

Abstract: Little is known about the dynamics and mechanisms of transitions between tonic firing and bursting in cortical networks. Here, we use a computational model of a neocortical circuit with extracellular potassium dynamics to show that activity-dependent modulation of intrinsic excitability can lead to sustained oscillations with slow transitions between two distinct firing modes: fast run (tonic spiking or fast bursts with few spikes) and slow bursting. These transitions are caused by a bistability with hysteresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 58 publications
7
77
0
Order By: Relevance
“…The origin of this feature is what one can call a subsequent self-induced depolarization in interaction with the exterior potassium. Note, this result is consistent with previously reported behavior of higher-dimensional quantitative models [19,20,21] …”
Section: B Modelsupporting
confidence: 93%
“…The origin of this feature is what one can call a subsequent self-induced depolarization in interaction with the exterior potassium. Note, this result is consistent with previously reported behavior of higher-dimensional quantitative models [19,20,21] …”
Section: B Modelsupporting
confidence: 93%
“…Epilepsy is a network disease involving interactions between many neurons, with pathological alterations in neuronal intrinsic excitability leading to epileptogenesis (2,6). Thus, it is important to understand how the network's structure can affect the chances to observe epileptic-like activity (10,29).…”
Section: Discussionmentioning
confidence: 99%
“…computational model | epilepsy | homeostasis | traumatic brain injury | paroxysmal discharge E pileptic activity in the brain emerges on several organizational levels from hyperexcitable dynamics of single neurons that result from genetic predisposition (1) or pathological alterations in extracellular ionic concentrations (2)(3)(4)(5)(6)(7)(8)(9) to aberrations in network structure that give rise to hypersynchronization of neuronal ensembles and subsequent onset of seizures (10). Such changes in network connectivity and structure may occur after severe brain trauma, which commonly leads to epileptogenesis (11).…”
mentioning
confidence: 99%
“…A computational model of large-scale neuronal network suggested that cortical deafferentation triggered homeostatic up-regulation of neuronal excitability and that was a sufficient factor of epileptogenesis (Fröhlich et al, 2005; Frohlich et al, 2006; Houweling et al, 2005; Volman et al, 2011). In vivo experiments showed that following cortical trauma, neuronal intrinsic currents are also modified to increase the neuronal excitability.…”
Section: The Trauma-induced Epilepsy Modelmentioning
confidence: 99%